Effective of several suppression procedures in eliminating a high-probability response in a severely brain damaged child - Ribes-Iñesta, Emilio; Guzmán, Eleazar (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The three different punishment procedures of time-out, electric shock and slaps were used to eliminate the highly undesirable behavior of the placing of nonedibles in the mouth by a severely retarded girl. All three punishment procedures were found effective in suppressing this response. However, in all three procedures it was found that the punishment situations were highly discriminated from those conditions of non-punishment, a finding that suggests some limitations in the use of punishment. It was also found upon a discontinuation of one of the punishers (electric shock) that the undesired response returned in strength above that level observed prior to the introduction of the shock.